The Explanation and answer is:
63t^(4)
3^(2)*7t^(4)
0 –1 (0, –1)
1 4 (1, 4)
2 9 (2, 9)
A.
y = 5x – 1
B.
y = –3x + 3
C.
y = 3x – 4
D.
y = 3x + 3
Answer:
Step-by-step explanation:
The given expression is
To complete the square, we first simplify the function to get:
Add and subtract the square of half the coefficient of x
The first three term is a perfect square
Hi!
This is an equilateral triangle. Meaning all sides equal the same.
A triangle's angles add up to 180.
60+60+60=180
Angle 2=60 degrees
-Seth